The Behavioral Response to Increased Pedestrian and Staying Activity in Public Space: A Field Experiment. Issue 1 (January 2022) - Zapata, Oscar; Honey-Rosés, Jordi
William Whyte originally hypothesized that the presence of people in a public space would attract more people. Contemporary planners now refer to "sticky streets" as places where pedestrians are compelled to linger and enjoy vibrant public life. We test the hypothesis that adding users to a public space will attract more people using an experimental design with confederates to add pedestrian movement and staying activity in a residential street for 45 randomly selected hours. We observed staying behavior by gender with and without our intervention. We find that the addition of public users reduced the total number of people staying in our study area, especially among women. We find that women's right to the city may be constrained by the mere presence of other individuals, even in safe spaces and during daylight hours. Our findings suggest that Whyte's claim is not universal, but depends on the conditions of a particular site.